2013
DOI: 10.1111/jcpt.12099
|View full text |Cite
|
Sign up to set email alerts
|

Risk of death associated with the use of conventional vs. atypical antipsychotic medications: evaluating the use of the Emilia-Romagna Region database for pharmacoepidemiological studies

Abstract: SUMMARYWhat is known and objective: Since 2005, a mounting base of evidence has identified that conventional antipsychotic medications are associated with an increased risk of mortality among elderly patients when compared to atypical antipsychotics. This study sought to explore the feasibility of using the EmiliaRomagna Region (RER) database for comparative safety analyses by replicating and refining risk estimates of this well-known drug safety example through meta-analysis. Methods: We identified a cohort o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Currently, the database contains more than 5 million individuals who were residents of the RER at any time during 2002 to 2013, including health care data of residents of the region who have gone outside the region to receive health care services. Prior publications offer additional details of the RER database and its use for health services research (29)(30)(31)(32).…”
Section: Data Sourcementioning
confidence: 99%
“…Currently, the database contains more than 5 million individuals who were residents of the RER at any time during 2002 to 2013, including health care data of residents of the region who have gone outside the region to receive health care services. Prior publications offer additional details of the RER database and its use for health services research (29)(30)(31)(32).…”
Section: Data Sourcementioning
confidence: 99%
“…At first glance, the observational findings appear convincing. The findings seem consistent, and chance cannot explain that multiple large studies reported an association between conventional antipsychotics and increased mortality risk. Moreover, sophisticated methods have been used to analyse the data.…”
Section: Introductionmentioning
confidence: 59%
“…During the following years, numerous observational studies replicated this finding . A meta‐analysis of eight of these studies yielded a hazard ratio of death of 1.35 (95%CI: 1.31–1.40) for users of conventional antipsychotics versus atypical antipsychotics . Moreover, the association has been found in general elderly populations, persons with dementia and residents of nursing homes.…”
Section: Introductionmentioning
confidence: 83%
“…The Regione Emilia‐Romagna administrative healthcare database for the period of 1 January 2002 through 31 December 2012 was used for the present study. The database is composed of linkable de‐identified demographic, hospital, all‐cause mortality and outpatient pharmacy data on individual prescriptions, and has been used extensively for the purposes of pharmacoepidemiologic research …”
Section: Methodsmentioning
confidence: 99%
“…The database is composed of linkable deidentified demographic, hospital, all-cause mortality and outpatient pharmacy data on individual prescriptions, and has been used extensively for the purposes of pharmacoepidemiologic research. 26,27 Patients discharged with at least one primary or secondary ICD-9 Clinical Modification (CM) diagnosis code (Online Appendix S1) for HNC cancer between 1 January 2003 and 31 December 2011 were identified as cases. The index date was defined as the date of discharge from the first hospital record containing a code for HNC.…”
Section: Me Thodsmentioning
confidence: 99%